Video Animasi Mesin Offset Sebagai Media Pembelajaran Cetak Offset - Rohmana, Toriqu Ahira; Ulfa, Saida; Adi, Eka Pramono (Universitas Negeri Malang, 2022)
The offset machine animation video is a product in the form of a learning video that facilitates and increases student motivation. Research and Development (R&D) or research and development is a research method used to produce products. The method used refers to Sadiman's model. The learning media developed contains Offset Printing subjects, Paper Transportation material on an Offset Machine. This product was developed for students of Graphic Production which is feasible to be applied in the learning process and has a complementary position, which means that it is designed and aimed at complementing the material to be conveyed in the learning process. The feasibility of this product has been tested by media experts, namely an Educational Technology lecturer and material expert, a productive subject teaching teacher with more than 10 years of experience in teaching and has found feasible criteria. The product has also been tested on students majoring in Graphic Production and the research has received a majority of positive responses. So it can be concluded that the animated video has the privilege of making it easier for students, increasing student attractiveness, and increasing student motivation in student learning activities hereby declared fit for use.Abstrak Video animasi mesin offset adalah sebuah produk berupa video pembelajaran yang memudahkan dan meningkatkan motivasi belajar siswa. Research and Development (R&D) atau penelitian dan pengembangan merupakan metode penelitian yang digunakan untuk menghasilkan produk. Metode yang digunakan mengacu pada model Sadiman. Media pembelajaran yang dikembangkan memuat mata pelajaran Cetak Offset materi Transportasi Kertas pada Mesin Offset. Produk ini dikembangkan untuk siswa Produksi Grafika yang layak diterapkan didalam proses pembelajaran dan berposisi menjadi pelengkap, yang berarti dirancang dan ditujukan melengkapi materi yang akan disampaikan dalam proses pembelajaran. Kelayakan produk ini telah diuji oleh ahli media adalah seorang dosen Teknologi Pendidikan dan ahli materi seorang guru pengajar matapelajaran produktif berpengalaman mengajar lebih dari 10 tahun dan mendapati kriteria layak. Produk juga telah diujicobakan kepada siswa jurusan Produksi Grafika dan penelitian mendapatkan tanggapan mayoritas positif. Sehingga dapat disimpulkan bahwa video animasi memiliki keistimewaan yaitu memudahkan siswa, menambah kemenarikan siswa, serta menambah motivasi siswa dalam aktifitas belajar siswa dengan ini dinyatakan layak digunakan.